Mutagenic, genotoxic and morphotoxic potential of different pesticides in the erythrocytes of Podocnemis expansa neonates - Pereira de Oliveira, Jose Silonardo; Vieira, Lucelia Goncalves; Carvalho, Wanessa Fernandes; Souza, Marcelino Benvindo de; Lima Rodrigues, Aline Sueli de; Simoes, Karina; De Silva, Daniela de Melo; Mendonca, Juliana dos Santos [UNESP]; Luz Hirano, Liria Queiroz; Quagliatto Santos, Andre Luiz; Malafaia, Guilherme (Elsevier B.V., 2020)
Despite the damaging effects of pesticides glyphosate (Gly), atrazine (Atra) and fipronil (lip) on different organisms, the mutagenic, genotoxic and morphotoxic potential of testudine erythrocytes in freshwater remains unknown. Thus, the aim of the present study is to assess the toxicological potential of these compounds in Podocnemis expansa (Amazonian turtles) neonates from eggs artificially incubated in substrate at different concentrations of herbicides Gly and Atra and insecticide Pip. Micronucleus test and other nuclear abnormalities, as well as comet assay and morphometric measurements taken of models circulating erythrocytes were used as toxicity biomarkers. Pups exposed to Gly (groups Gly-65 ppb and Gly-6500 ppb) were the ones recording the largest amount of nuclear abnormalities; erythrocytes with multilobulated, notched and displaced nucleus were mostly frequent in groups Atra-2 ppb and Gly-65 ppb. All treatments (Gly-6500 ppb, Atra-2 ppb, Atra-200 ppb, Fip-4 ppb and Fip-400 ppb), except for group Gly-65 ppb, led to decreased erythrocyte area, increased nuclear area: erythrocyte area ratio, as well as to decreased erythrocyte and erythrocyte nuclei circularity, which highlights the clear effect on the size and shape of these cells. On the other hand, the cornet assay did not evidence any genotoxic effect caused by the assessed pesticides. This is a pioneer study on the mutagenic and morphotoxic potential of pesticides in P. expansa eclodides exposed in ovo to Gly, Atra and Fip; therefore, it is an insight on how these compounds can affect the health of these animals. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Pesticides; Ecotoxicology; Mutagenicity; Genotoxicity; Morphotoxicity